Empowering employee behavior and organizational transformation for lasting impact - Sitorus, Sandy Fransiska; Suryana, Asep; Rizal, Edwin (Jurnal Praksis dan Dedikasi Sosial, 2025)
This study delves into the intricate relationship between employee behavior and the efficacy of organizational changes within Balai Besar Bahan dan Barang Teknik, under the Indonesian Ministry of Industry. Employing a quantitative methodology, the research engaged with 32 dedicated employees at Balai Besar Bahan dan Barang Teknik, Ministry of Industry, uncovering valuable insights. These insights illuminate the critical role of employee behavior in shaping the brand's resonance and organizational transformation. The study reveals a web of correlations: a positive link between employee voice and change effectiveness, a negative association between employee exits and performance, an adverse connection between neglect and job satisfaction, and a robust bond between employee loyalty and resilience. These findings signify that within the Balai Besar Bahan dan Barang Teknik narrative, the employees who voice their concerns are more likely to perceive organizational changes as effective, bolstering brand awareness. Conversely, employees contemplating an exit demonstrate diminished performance, underscoring the pivotal role of employee engagement in upholding the brand's strength. Employee neglect points to a potential dent in job satisfaction, an aspect integral to brand loyalty. Moreover, unwavering employee loyalty is a cornerstone for resilience in the face of change, vital for brand continuity and brand awareness. In the larger context, these findings hold profound implications for policymakers and practitioners engaged in the realm of organizational change. The insights gleaned provide the foundation for strategic policies that encourage employee voice and reinforce brand loyalty, resulting in increased brand awareness. Practitioners can leverage these insights to craft change management strategies that dismantle resistance, ensuring successful change implementation and further enhancing brand recognition.